Insights into nutrition education: a qualitative interpretive meta synthesis from the Latin American perspective - Pava-Cárdenas, Alexandra; Alzate-Yepes, Teresita; Cervato-Mancuso, Ana Maria (O Mundo da Saúde, 2024)
Studies about health education have focused more on what is taught than on who is learning. This article reports the findings of a qualitative interpretive meta-synthesis (QIMS) on patients’ experiences which emerge during participation in educational interventions on food and nutrition in Latin America. A search for studies based on constructivist, hermeneutic or interpretive paradigm published between 2006 and 2020 encompassing nine databases was conducted, identifying 1,676 records. Three stages were contemplated: I) identification of the sample through characterization and quality assessment forms, resulting in nine studies; II) extraction of themes addressed in the research results to understand the participation experiences, and III) translation of data and synergistic comprehension through an integration of experiences, including a new categorization of themes. The QIMS generated seven themes: "social conflict", "insecurity", "sacrifice", "care", "valuing the approach", "change in understanding" and "learning". Given the level of detail regarding the social reality in which participation occurs, the themes highlight three dimensions that are crucial in food and nutrition education from the patients’ perspective: "life history", "food configuration" and "educational appreciation". The complexity of patient experiences demands an approach that better acknowledges the configuration within the encountered dimensions. This necessitates exploring how individual patient experiences relate to the broader context of nutrition and food education in the Latin American region.